1987
DOI: 10.1111/j.1365-2621.1987.tb14034.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Instrumental Analyses of Warmed‐Over Flavor in Beef

Abstract: Raw, freshly cooked, stored and recooked beef muscle samples were assessed by chemical, instrumental and sensory methods of analyses for flavor quality, with particular emphasis on warmed-over flavor (WOF). The character notes used by a trained sensory panel to describe WOF were cardboardy, rancid, stale, and metallic. Samples analyzed by direct gas chromatography utilizing either packed or fused silica capillary columns showed that compounds usually associated with lipid oxidation reactions could be used as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…A 9-point Hedonic scale (where 1 is dislike extremely and 9 is like extremely) was used to evaluate sensory attributes of patties. For estimating the saturated (SFA) and unsaturated fatty acids (USFA) and their ratio, total lipids from sample were extracted according to the method of Angelo et al (1987) and methyl esters were prepared by the method of Luddy et al (1968). Methyl esters of fatty acids were separated in a gas chromatograph (Nucon-5765, Mumbai, India) equipped with fl ame ionization detector.…”
Section: Methodsmentioning
confidence: 99%
“…A 9-point Hedonic scale (where 1 is dislike extremely and 9 is like extremely) was used to evaluate sensory attributes of patties. For estimating the saturated (SFA) and unsaturated fatty acids (USFA) and their ratio, total lipids from sample were extracted according to the method of Angelo et al (1987) and methyl esters were prepared by the method of Luddy et al (1968). Methyl esters of fatty acids were separated in a gas chromatograph (Nucon-5765, Mumbai, India) equipped with fl ame ionization detector.…”
Section: Methodsmentioning
confidence: 99%
“…The nature of the off-odor depends on the types of microorganisms growing and those will be determined by such factors as the temperature of storage and the nature of product (fresh, cured and comminuted). It is generally accepted that autoxidation of membrane of phospholipids is largely responsible for the development of off-odour [47] . However, Calkins and Hodgen [48] reported that diets high in polyunsaturated fatty acids may be contributing to the appearance of off-flavors in fresh beef muscles.…”
Section: Change In Beef Flavour During Storagementioning
confidence: 99%
“…16,17) Being a potential autoxidation product of linoleic acid, 18) 2-pentylfuran showed the highest ratio of concentration in warmed-over flavor beef to freshcooked beef, 19) and a higher relative concentration of 2-pentylfuran was detected in this study. Besides, dodecane and 2,4-decadienal were identified in cooked longissimus muscle from different breeds by Lu et al 6) For 3-methyl-1-butanol, it could give an olfactory sensation of fresh-cured pork flavor in short ripening process.…”
Section: Breedmentioning
confidence: 47%